“What We’ve Said Can be Proven in the Ground”: Stó:lō Sovereignty and Historical Narratives at Xá:ytem, 1990–2006 - Knickerbocker, Madeline (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
Less than a month after the conclusion of the Oka crisis in Québec in the fall of 1990, development threatened another Indigenous heritage site, this one on the outskirts of Mission, British Columbia. Workers were preparing to blast apart a large stone and clear land for a 14-house subdivision on a sloping hill near the Fraser River. Indigenous elders, along with archaeologists and activists, responded rapidly by stepping forward to challenge the destruction of the site. Xá:ytem, the stone, is a sacred site for Stó:lō peoples, who have been living in the area for millennia. This paper examines the struggle to save Xá:ytem to reveal the tactical hybridity that can emerge when conceptions of heritage are entangled with expressions of sovereignty. When situated in the context of other Indigenous protests, analysis of the historical narratives deployed at Xá:ytem reveals much about the surprising and tenacious nature of heritage activism in late twentieth-century Canada.